2021
DOI: 10.1182/blood-2021-148451
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Safety and Efficacy Data from Patients (Pts) with Relapsed/Refractory (R/R) B-Cell Malignancies Treated with the Novel B-Cell Lymphoma 2 (BCL2) Inhibitor BGB-11417 in Monotherapy or in Combination with Zanubrutinib

Abstract: Background: BCL2, a key regulator of apoptosis, is aberrantly expressed in many hematologic malignancies, which can lead to pathologic cancer cell survival. BCL2 inhibitors have been shown to be safe and effective, resulting in their approval for the treatment of pts with chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) and acute myeloid leukemia. Treatment with the currently approved BCL2 inhibitor, venetoclax, can be limited by common gastrointestinal toxicities, neutropenia, and the emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…We further identified 11 clinical trials of CLL ( N = 9), mantle cell lymphoma (MCL) ( N = 1), and Waldenstrom's Macroglobulinemia ( N = 1) (Table 3). 24,45–55 There were two Phase I trials, seven Phase II trials, and two Phase III trials 24,45–55 . The dose of ibrutinib ranged from 140 to 560 mg daily.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We further identified 11 clinical trials of CLL ( N = 9), mantle cell lymphoma (MCL) ( N = 1), and Waldenstrom's Macroglobulinemia ( N = 1) (Table 3). 24,45–55 There were two Phase I trials, seven Phase II trials, and two Phase III trials 24,45–55 . The dose of ibrutinib ranged from 140 to 560 mg daily.…”
Section: Resultsmentioning
confidence: 99%
“…We identified three clinical trials that assessed zanubrutinib in R/R B cell lymphoma, R/R MCL, and Waldenstrom's macroglobulinemia (Table 3). 56,64,65 One study reported nonfatal TLS in a single patient being treated for R/R B cell lymphoma with a combination of zanubrutinib and BGB‐11417 (bcl2 inhibitor) 53 . None of the studies used TLS prophylaxis and no information was provided regarding TLS treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adverse events included atrial fibrillation (17%), grade 3/4 neutropenia (17%) and thrombocytopenia (8%). Early results from a phase 1 study of zanubritinib in combination with BGB-11417 (a selective BCL2 inhibitor) has demonstrated excellent tolerability with no grade ≥3 events, although efficacy has not yet been established due to short follow up [ 76 ]. Phase 3 studies are currently investigating this combination in relapse and upfront therapy, predominantly in CLL and MCL [ 77 , 78 ].…”
Section: Review Of Approved Small Molecule Inhibitorsmentioning
confidence: 99%